The Extent to Which the Content of the University Curriculum Inculcates an Entrepreneurial Mind Set - Daniel Madzanire; Doreen Nkala; Tsuu Faith Machingura (Great Zimbabwe University, School of Commerce, 2023)
Graduates emerge from educational institutions yearly. Through entrepreneurship education, the media and society are raising questions about whether or not universities are providing students with sufficient knowledge and the necessary skills to boost the economy of the country. The purpose of this paper was to investigate the extent to which the content of a university's curriculum inculcated entrepreneurial mind sets in university students. As a consequence of this, the intention of this study was to investigate whether or not the content of the curriculum taught in universities increased the desire of students to begin their very own businesses. The investigation used both explanatory and descriptive research designs, and it also included a case study. The sample size for the research was decided to be 189 different students. The research employed non-probability sampling methods as well as probability sampling methods, in particular stratified sampling methods and convenience sampling methods. In-depth interviews and questionnaires were used to collect the data for this study. The research that demonstrated that the nature of the instruction provided in an entrepreneurial program has a significant impact on the number of people who choose to pursue entrepreneurial endeavors. Students in higher education should be encouraged to think of themselves as potential business owners through the implementation of an entrepreneurship curriculum that should be standard across all departments.